Existence as a Real Property The Ontology of Meinongianism - Berto, Francesco; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This profound exploration of one of the core notions of philosophy the concept of existence itself reviews, then counters (via Meinongian theory), the mainstream philosophical view running from Hume to Frege, Russell, and Quine, summarized thus by Kant: Existence is not a predicate. The initial section of the book presents a comprehensive introduction to, and critical evaluation of, this mainstream view. The author moves on to provide the first systematic survey of all the main Meinongian theories of existence, which, by contrast, reckon existence to be a real, full-fledged property of objects that some things possess, and others lack. As an influential addition to the research literature, the third part develops the most up-to-date neo-Meinongian theory called Modal Meinongianism, applies it to specific fields such as the ontology of fictional objects, and discusses its open problems, laying the groundwork for further research. In accordance with the latest trends in analytic ontology, the author prioritizes a meta-ontological viewpoint, adopting a dual definition of meta-ontology as the discourse on the meaning of being, and as the discourse on the tools and methods of ontological enquiry. This allows a balanced assessment of philosophical views on a cost-benefit basis, following multiple criteria for theory evaluation. Compelling and revealing, this new publication is a vital addition to contemporary philosophical ontology.
Prologue: Much Ado About Nothing -- Acknowledgments -- Existence as Logic -- Chapter 1. The Paradox of Non-Being -- Chapter 2. To Exist and to Count -- Chapter 3. Troubles for the Received View -- Nonexistence -- Chapter 4. Existence As a Real Property -- Chapter 5. Naïve Meinongianism -- Chapter 6. Meinongianisms of The First, Second, and Third Kind -- Close Encounters (with Nonexistents) of the Third Kind -- Chapter 7. Conceiving the Impossible -- Chapter 8. Nonexistents of The Third Kind at Work -- Chapter 9. Open Problems -- References -- Index.
Keywords: Philosophy (General).; Metaphysics; Ontology; Philosophy; Metaphysics; Ontology; History of Philosophy